Namburbi Texts in the British Museum. I - Caplice, Richard I.
to be continued; 1. Namburbi Catalogues: 1. K. 2389; 2. K. 3277; 3. K. 10664; 4. Rm. 2,178; 5. K. 9718; II. Smaller Fauna: 6. K. 3365; 7. K. 5944; 8. 81-7-27, 247; 9. K. 9789; III. Domestic Animals: 10. A) LKA 114; B) DT 90; C) STT 72; 11. K. 2577.